Comparison of the Effects of Pregnancy Exercise Using Coaching and Leaflet Methods on Anxiety Levels in Second-Trimester Primigravida Pregnant Women as Preeclampsia Prevention Efforts (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Background: Preeclampsia is a serious complication during pregnancy that poses significant risks to both maternal and fetal health. Psychological stress and anxiety in expectant mothers are known contributors to the onset of this condition. Engaging in pregnancy exercise has been shown to help alleviate anxiety symptoms; however, the degree of effectiveness can vary depending on the method of instruction used to deliver the exercise program. This research aimed to evaluate and compare the impact of two different educational approaches—coaching and leaflet-based methods—on anxiety reduction in primigravida women during their second trimester. The study applied a quasi-experimental design with a pretest-posttest control group framework. A total of 30 primigravida participants were selected and evenly assigned to either the intervention group, which received guided pregnancy exercise through the coaching method, or the control group, which followed instructions via printed leaflets. Anxiety levels before and after the intervention were assessed using the Hamilton Anxiety Rating Scale (HARS). Findings demonstrated a statistically significant decrease in anxiety levels in both groups following the intervention. However, the group that participated in the coaching-based pregnancy exercise showed a more pronounced reduction in anxiety scores compared to those who used the leaflet method (p < 0.05). Pregnancy exercise guided by the coaching approach proved to be more effective in lowering anxiety among second-trimester primigravida women than exercises guided by informational leaflets. Incorporating coaching-based pregnancy exercise into prenatal care could serve as a valuable promotive and preventive strategy for reducing the risk of preeclampsia.